PROTEST ACTIONS AND POLITICAL OPPORTUNITIES IN THE GOVERNMENT OF LUIS GUILLERMO SOLÍS (2014-2018) - Alvarado Alcázar, Alejandro (2020)
This paper shows the results of a systematic work of monitoring social protest in Costa Rica during the four-year term of the government of Luis Guillermo Solís (May 2014-May 2018), using the Protest Event Analysis (aep) methodology. The document is structured in two parts. The first focuses on describing and characterizing the general tendencies of the protest during the study period, it looks at the protest repertoires, the demanding actors, the demands and the demanded actors. From this part, it is concluded that the protest actions decreased year after year and that the strategies and action routines were differentiated according to the demands. The second part proposes exploring the relationship between the reduction of protest actions and the political opportunities opened by the Solis government as a working hypothesis for future research.